(untitled) - Kee, Joyce LeFever (St. Louis, Missouri, 2015)
Prepare to administer drugs safely by mastering key pharmacology concepts and drug calculation skills! Pharmacology: A Patient-Centered Nursing Process Approach, 8th Edition covers nursing pharmacology within a real-world nursing context. Using a clear, streamlined approach, this text makes it easier to understand pharmacology with a detailed unit on dosage calculations, a nursing process framework for drug therapy, and summaries of prototype drugs. Written by nursing educators Joyce Kee, Evelyn Hayes, and Linda McCuistion, this edition includes a strong QSEN focus, enhanced coverage of prioritization, and more NCLEX® Examination–style questions on the subject of pharmacology.
Keywords: Drug Therapy,Hiện tượng dược lý,Thuốc điều trị,Pharmacological Phenomena; Nurses' Instruction,Chỉ dẫn điều dưỡng,Chỉ dẫn điều dưỡng,Nurses' Instruction